Implementasi Program Pra Siaga dalam Menumbuhkan Karakter di RA Mutiara Bunda - Munakhiroh El Hajar; Ainun Haiva Nabila; Siskha Putri Sayekti (AZKIA: Journal of Islamic Education in Asia, 2024)
Character education from an early age is crucial in creating a generation with noble morals, and this character education can be acquired through pre-school activities. The aim of this research is to understand character development in early childhood education programs at RA Mutiara Bunda, comprehend the utilization of character development in early childhood education activities, and evaluate behavioral development in early childhood education activities. The research findings indicate the following: (1) Enhancing learning behavior through play in the preschool period, with plans for daily lesson implementation, full-week lesson plans, and preschool learning. (2) Developing learning behavior in the preschool period through play, including enhancing independent behavior and responsibility through discipline agreed upon by children and teachers, and providing rewards or minor punishments at the end of activities, laying foundations by acting in the preschool period and group games; confidence; Encouraging participation and fostering children's creativity through group games. (3) Work evaluation includes character traits such as independence, responsibility, and confidence, which according to teachers, are consistent with performance. However, based on teacher assessments, integration and testing of self-confidence and independence still need to be strengthened. The development of children in Group B participating in pre-school activities is at the expected level.